Pharmacokinetics of combination antiparasitic drug preparation for dogs and cats in the form of spot-on solution - Arisov, Mikhail Vladimirovich; Indyuhova, Evgenia Nikolaevna; Arisova, Gulnara Bakitovna (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The object of the study was to examine the major pharmacokinetic parameters after a single application of a complex drug preparation for veterinary use based on fipronil, praziquantel, moxidectin, and pyriproxyfen in cats and dogs. Materials and Methods: For dogs, the drug preparation was administered spot-on solution in the following dosage of active pharmaceutical substances: fipronil 27.0 mg/kg body weight (bwt), praziquantel 10.8 mg/kg bwt, moxidectin 6.75 mg/kg bwt, and pyriproxyfen 5.4 mg/kg bwt; for cats, the dosage was the following: fipronil 43.2 mg/kg bwt, praziquantel 17.28 mg/kg bwt, moxidectin 4.32 mg/kg bwt, and pyriproxyfen 8.64 mg/kg bwt. The blood samples were taken from dogs and cats. The principle of the method for determining praziquantel, trans-4-hydroxypraziquantel, pyriproxyfen, and fipronil in serum samples was chromatographed in a high-pressure liquid chromatograph with detection by means of a mass-spectrometric detector. The moxidectin content of the blood was detected by high-performance liquid chromatography. Results: The drug preparation active substances: praziquantel, fipronil, and moxidectin are absorbed into the blood of dogs and cats. The penetration of praziquantel into the systemic circulation and further into organs and tissues was proved. After topical administration, moxidectin is absorbed and distributed systemically and is slowly removed from the plasma, which manifests itself in detectable concentrations of moxidectin in the blood for 1 month. Conclusion: The present results of pharmacokinetic investigations may promote to the determination of effective therapy strategy and prophylaxis of parasitic diseases in dogs and cats. J. Adv. Vet. Anim. Res., 6(1): 25-32, March 2019